Implementation Of Teacher Performance Innovations In Improving The Quality Of Education At Sma Negeri 1 Donggo - Rahman, Arif; Umar, Umar; Subari, Subari (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research is a qualitative research using a narrative descriptive approach to analyze data. To obtain data or information, the researcher directly visited the respondents using data collection techniques; observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data and verifying/drawing conclusions. Based on the exposure of data and research findings, the results of the research were obtained, namely: (1) There are 5 innovations in teacher performance in improving the quality of education at SMA Negeri 1 Donggo, including: improving teacher competence, teachers' religious spiritual activities, forming work teams, implementing work discipline and awarding. Keywords: Implementation, Innovation, Teacher Performance. (2) The implementation of teacher performance innovations in improving the quality of education at SMA Negeri 1 Donggo includes: a) improving teacher competence, b) teachers' religious spiritual activities c) the formation of work teams, namely curriculum teams, d) the implementation of work discipline through the implementation of teachers' attendance and daily journals and e) the provision of rewards in the form of allowances and positions. (3) The results of teacher performance innovations in improving the quality of education at SMA Negeri 1 Donggo include: a) the competence and performance of teachers in carrying out their duties are getting better, b) the formation of high student character c) high academic and non-academic achievement of students d) high quality exam results and graduates, and e) increasing the support of parents and the community.